2018
DOI: 10.15537/smj.2018.11.23026
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of emergency department staff towards disaster and emergency preparedness at tertiary health care hospital in central Saudi Arabia

Abstract: Objectives:To assess the knowledge, practices, and attitudes regarding disaster and emergency preparedness among Emergency Department (ED) staff.Methods:This cross-sectional study was conducted at Tertiary health care hospital in central Riyadh, Kingdom of Saudi Arabia. A self-administered survey was utilized to collect data from ED physicians and nurses. The questionnaire was divided into 5 sections viz; demographics, knowledge about disaster management and preparedness, attitudes about disaster planning, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 15 publications
8
60
2
1
Order By: Relevance
“…These make nurses with less work experience both more aware of the disasters and disaster management, and better perform in this area. These results were in agreement with those of the studies conducted by Nofal et al (2018) [19], and Soltani et al (2016) [17]. However, the results of the present study were not similar to those of Jiang et al (2003), Adenekan et al (2016) [20], Sonneborn et al (2018) [21], Imani et al (2011) [4], and Azadi et al's (2018) [12] studies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These make nurses with less work experience both more aware of the disasters and disaster management, and better perform in this area. These results were in agreement with those of the studies conducted by Nofal et al (2018) [19], and Soltani et al (2016) [17]. However, the results of the present study were not similar to those of Jiang et al (2003), Adenekan et al (2016) [20], Sonneborn et al (2018) [21], Imani et al (2011) [4], and Azadi et al's (2018) [12] studies.…”
Section: Discussionsupporting
confidence: 80%
“…As a result, younger nurses are more aware of the disasters and disaster management, and have better performance at the time of disasters. These results are in line with those of the research by Soltani et al (2016) [17], but not with the findings obtained by Ahayalimudin et al (2016) [18], Nofal et al (2018) [19], Jiang et al (2015) [16], Azadi et al (2018) [12], and Imani et al (2011) [4], which indicated no significant relationships between knowledge and performance, and the studied samples' age. This contradiction can be related to the differences in the mean age of the samples investigated in these studies.…”
Section: Discussionsupporting
confidence: 80%
“…The survey response indicates significant statistical difference of self‐regulation scores with respect to nursing education ( p ‐value = .033). The literature provides evidence for these findings such as research by Nofal, Alfayyad, Khan, Al Aseri, and Abu‐Shaheen () which indicated that education develops the individual necessary knowledge related to the disaster emergency preparedness, which further highlights its need. Öztekin, Larson, Yüksel, and Altun Uğraş () also stated that maturation of the students’ knowledge related to disasters preparedness develops through increased education.…”
Section: Discussionmentioning
confidence: 92%
“…The healthcare section, especially hospitals, play the most significant role in the primary stages of emergencies and disasters. Therefore, the increased preparedness of healthcare systems for identifying risks and responding appropriately to disasters is of utmost importance [8]. Preparedness of hospitals against natural disasters influences their performance in the best care provision and increases their capacity for suitable responding in these conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Preparedness of hospitals against natural disasters influences their performance in the best care provision and increases their capacity for suitable responding in these conditions [9]. The global reports stated that the approval of plans and policies, designing and building resilient hospitals at the national level, assessment of hospital safety, education, protection of personnel and equipment, and strategic planning for emergency responding are among the facilities and approaches for safe care provision [8]. Moreover, the presence of response policy and standard practical guide for emergency hospital activities in internal and external events are influential in hospital preparedness against natural disasters [7].…”
Section: Introductionmentioning
confidence: 99%